Effect of Anodal Transcranial Direct Current Stimulation Combined With Cognitive Training for Improving Cognition and Language Among Children With Cerebral Palsy With Cognitive Impairment: A Pilot, Randomized, Controlled, Double-Blind, and Clinical Trial - Ko, Eun Jae; Hong, Mi Jin; Choi, Eun Jung; Yuk, Jin Sook; Yum, Mi Sun; Sung, In Young (Frontiers in Pediatrics, 2021)
About 30-45% of cerebral palsy (CP) patients have cognitive impairment. Previous studies showed the evidence that transcranial direct current stimulation (tDCS) may have some benefits in attention-deficit/hyperactivity disorder, autism spectrum disorder, and motor development in CP. The aim of this study is to evaluate the effect of tDCS on cognition, language, and activities of daily living (ADL) among children with CP with cognitive impairment. It was a pilot, randomized, controlled, double-blind, clinical trial in a tertiary pediatric hospital, and 13 children with CP and a cognitive age under 42 months were enrolled. tDCS group (n=8) had active tDCS and cognitive training (20 min/session, total 20 sessions, for 12 weeks) and sham group (n=5) had sham tDCS and cognitive training. Primary outcome was the Bayley Scales of Infant Development II (BSID II). Secondary outcomes were the Pediatric Evaluation of Disability Inventory (PEDI), the Laboratory Temperament Assessment Battery (Lab-TAB), the Early Childhood Behavior Questionnaire (ECBQ), the Korean version of MacArthur–Bates Communicative Development Inventories (M-B CDI-K), the Sequenced Language Scale for Infants (SELSI) and the Preschool Receptive-Expressive Language Scale (PRES). After intervention, the tDCS group showed significant improvements in all measurements (p<0.05) except the M-B CDI-K (grammar), whereas the sham group only showed significant improvements in the Lab-TAB (manipulation domain), the ECBQ (attentional shifting), and the M-B CDI-K (comprehension). The between-group differences in the degree of post-intervention improvement were not statistically significant. The degree of improvement was associated with better baseline cognitive function and younger age (p<0.05). There were no major adverse events after tDCS. The combined application of tDCS and cognitive training was feasible and associated with improvements in cognitive function, ADL, and language among children with CP with cognitive impairment. However, considering that it is a pilot study, further larger-scale systematic investigation is needed.